The Effect of Servant Leadership on Employee Performance as Mediated by Leader-Member Exchange and Organizational Citizenship Behavior - ., Kartono; Setiawan, Margono; ., Sunaryo; Moko, Wahdiyat (KnE Social Sciences, 2023)
This study aimed to determine the role of leader-member exchanges and organizational citizenship behavior as mediating variables in the relationship between servant leadership and employee performance. Data were analyzed using Structural Equation Modeling (SEM). The results of this study demonstrated that servant leadership, leadermember exchange and organizational citizenship behavior had positive and significant effects on employee performance. Also, servant leadership positively and significantly affected leader-member exchange. Additionally, servant leadership had a positive and significant effect on organizational citizenship behavior. The indirect impact of servant leadership on employee performance through leader-member exchange was significant. Lastly, the indirect effect of servant leadership on employee performance through organizational citizenship behavior was significant. Keywords: Servant Leadership, Leader Member Exchange, Organizational Citizenship Behavior, Employee performance, PT. Bank Artha Graha Internasional Tbk.